ANALISIS KEBIJAKAN PENDIDIKAN FULL DAY SCHOOL DI SD IT DELI INSANI TANJUNG MORAWA - Sri Aqilah Maulida; Asnil Aidah Ritonga (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2026)
This research aims to analyze the full day school policy at SD IT Deli Insani Tanjung Morawa. This type of research uses qualitative research with a phenomenological approach. Primary data sources are obtained through direct observations, in-depth interviews with teachers, students, foundation staff, and head of school. Secondary data resources are obtaining from books, journals, and other related articles. Data analysis techniques use content analysis with methods of reduction, presentation, and conclusion. Research results show that SD IT Deli Insani Tanjung Morawa has implemented the full day school policy since 2005 based on instructions from the Integrated Islamic School Network (JSIT). SD IT Deli Insani Tanjung Morawa also offers a variety of outstanding activities such as morning activity, tahsin tahfidz, routine training, Islamic Private Building (BPI) program, and extracurricular activities to support student self-development in a comprehensive way. The response of students and parents to this policy tends to be positive, with a feeling of a pleasant school atmosphere and a variety of extracurricular activities. Parents' support for this policy is due to school schedules that match their working hours and high confidence in the quality of education. However, the main constraints are high school costs and transportation barriers that some parents face because they have to adjust their children's pickup schedules, which now end longer. The research concludes that the implementation of the full day school policy at SD IT Deli Insani Tanjung Morawa contributes to meeting the needs of Islamic religious education, improving the quality of education, as well as providing a diverse and attractive learning environment for students.